The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9030612
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cytology in the Diagnosis of Basal Cell Carcinoma Subtypes

Abstract: Background: Basal cell carcinoma (BCC) is the most common skin cancer in the white population. Nonsurgical treatments are first-line alternatives in superficial BCC (sBCC); therefore, differentiating between sBCC and non-sBCC is of major relevance for the clinician. Scraping cytology possesses several advantages, such as an earlier diagnosis and scarring absence, in comparison to a biopsy. Nevertheless, previous studies reported difficulties in differentiating the different BCC subtypes. The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In cases of dermoid cysts or implantation cysts, the smear showed a mixture degenerated epithelial cells and keratinous material, a picture found also by [16], but the cell block also usually failed due to the keratinous material.In cases of atypical lipomas, FNAC smear showed a very useful picture; pleomorphic, hyperchromatic lipoblasts, mucoid background; the cell block did not add a more information. In cases of basal cell carcinoma; FNAC smear showed malignant cells with basophilic cytoplasm; the same results were found by [17], but the orientation of cells appeared in the cell block with peripheral palisading. In cases of squamous cell carcinoma, the malignant epithelial cells and the individual cell keratinization appeared in the smear.…”
Section: Discussionsupporting
confidence: 75%
“…In cases of dermoid cysts or implantation cysts, the smear showed a mixture degenerated epithelial cells and keratinous material, a picture found also by [16], but the cell block also usually failed due to the keratinous material.In cases of atypical lipomas, FNAC smear showed a very useful picture; pleomorphic, hyperchromatic lipoblasts, mucoid background; the cell block did not add a more information. In cases of basal cell carcinoma; FNAC smear showed malignant cells with basophilic cytoplasm; the same results were found by [17], but the orientation of cells appeared in the cell block with peripheral palisading. In cases of squamous cell carcinoma, the malignant epithelial cells and the individual cell keratinization appeared in the smear.…”
Section: Discussionsupporting
confidence: 75%
“…Predicting the recurrence risk of BCCs before treatment had always been a research hotspot. Pasquali et al 4 use cytology to diagnosis superficial BCC, which is susceptible of nonsurgical treatment, and found an inverse correlation between the diagnosis of superficial BCC and the presence of mucus, dehiscence, and atypical grade in the basal cells. Wortsman et al 14 reported that a higher hyperechoic spots count was found in high‐risk BCCs, with sensitivity of 79% and specificity of 53% for predicting high‐risk BCCs using cut‐off point ≥7 hyperechoic spots.…”
Section: Discussionmentioning
confidence: 99%
“…3 Preoperative biopsy is mainly used to identify highrisk from low-risk BCC in clinical practice, but biopsy requires manipulation of the sample and often leave scarring, which is best avoided if BCC is susceptible to nonsurgical treatment, especially on the face. 4 Furthermore, preoperative biopsy represents only one sample of the tumor and may not include all the histological characteristics of the entire lesion. 5 A new noninvasive technique to determine the risk of BCC recurrence prior to treatment will undoubtedly be of great help in the development of clinical treatment plans.…”
mentioning
confidence: 99%
“…To our knowledge, the most commonly described sample collection technique is scrape cytology. With this technique, the tissue is obtained by scraping the tumor or scratching a part of the lesion off, both performed with a scalpel blade (5,6). Imprint smear cytology is a useful alternative for easily exfoliating ulcerated lesions.…”
Section: Description Of the Techniquementioning
confidence: 99%